INTERNAL INFORMATION SYSTEM FOR ADMINISTRATIVE FACILITATION AT EPISKOP KONSTANTIN PRESLAVSKI UNIVERSITY OF SHUMEN: INTERNAL INFORMATION SYSTEM FOR ADMINISTRATIVE FACILITATION AT EPISKOP KONSTANTIN PRESLAVSKI UNIVERSITY OF SHUMEN - Petkova-Kaleva, Stefka; Tsoneva, Korneliya; Tsonev, Tsonyo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article describes the policy at Shumen University regarding the collecting and analysis of information about the issues pertaining to the continuous application of the System for Ensuring the Quality of Education. The subject of the analysis is the participation of the interested parties in the development of the System. The various methods for collecting information depending on its purpose are discussed.